Social and Psychological Features of Hardiness in Personality of Students of Higher Education Institutions - Zara A-M., Albakova (2020)
The topicality and significance of the study is determined by the fact that life and activity of a person in contemporary socio-economic conditions are inextricably connected with the constant impact of adverse social, political, economic and other factors on him. These factors are accompanied by the emergence of various kinds of difficult life situations, as a result of which stress develops in a person. In the student milieu, stress arises under the influence of difficulties associated with both the learning process and life circumstances. The paper presents the results of an empirical study of socio-psychological features of hardiness in students of higher educational institutions. The methods of research comprised: theoretical analysis, empirical research (testing), qualitative analysis of the obtained data, mathematical and statistical data processing (SPSS Statistics, Excel). Testing included the following psycho-diagnostic tools: the author’s questionnaire for assessing stressful situations; McCrae-Costa Five-Factor Personality Questionnaire (The Big Five dimensions); “Hardiness test”; Self-attitude technique. The validity and reliability of the study results was ensured by the initial methodological positions, the use of proven tools, sample representativeness of the research, as well as mathematical processing of data with the use of a software package for statistical analysis. As a result of the study, it was proved that emotion-focused ways of overcoming stress associated with a decrease in tension and a change in attitude to emerging difficulties prevail among the students of both the experimental and control groups. A high level of stress was found in the majority of subjects. In order to reduce this stress, it is necessary for students to form special skills to overcome it. In addition, an analysis of the psychological factors of students’ hardiness made it possible to determine the main areas of their psychological support in overcoming difficult life situations (development of qualities that form the core of students’ personal adaptive potential, the formation of their social competency, enrichment of social networks, as well as learning ways to find and accept social support).